UJI EFEKTIVITAS DAN KEAMANAN KOMBINASI METFORMIN-VILDAGLIPTIN PADA DIABETES MELITUS TIPE 2 DI RSPAL Dr. RAMELAN SURABAYA - Dwi Octamy Sari; Amelia Lorensia; Abdul Rahem; Lestiono Lestiono (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Metformin is the first-line therapy for Diabetes Mellitus (DM), which has not been able to control blood glucose in type 2 DM. One of the Dipeptidyl Peptidase IV Inhibitor (DPP4-I) groups, namely vildagliptin, has been included in the National Formulary which is used as a combination for the therapy of DM patients Type 2. Research objectives to know the effectiveness and safety of the combination of metformin-vildagliptin in type 2 DM at RSPAL Dr. Ramelan Surabaya. This research method uses a quantitative method with an observational study design, with retrospective data collection based on the Medical Records of Type 2 DM patients who first received metformin-vildagliptin combination therapy (n = 30) carried out observations, and recorded the results of Fasting Blood Glucose (GDP) examinations, Postprandial 2-hour blood glucose (GD2JPP), and HbA1C at baseline and after 3 months of therapy, and observed the safety of the combination. Results The metformin-vildagliptin combination reduced GDP 33.13 ± 40.73 mg/dL, GD2JPP 34.30 ± 48.81 mg/dL, and HbA1C 0.89 ± 0.86%. Did not show any side effects of hypoglycemia, but 3.33% experienced nausea/vomiting and dyspepsia. It was concluded that the combination of metformin-vildagliptin was able to reduce GDP, GD2JPP, and HbA1C,